Celery Juice as a Gate Control Theory-Based Nursing Intervention for Chronic Pain in Hypertensive Older Adults: A Quasi-Experimental Community Health Study - Zahrotul Fithria; Bagus Dwi Cahyono; Nurul Huda; Nadia Rohmatul Laili; Sri Wahyuni (Tarqabin Nusantara Group, 2026)
Chronic pain is a common yet under-recognized complication of hypertension, resulting from sustained vascular stress, sympathetic overactivity, and impaired tissue perfusion. Celery juice (Apium graveolens) has been proposed as a nonpharmacological adjunct to interrupt this pain–pressure cycle, but community-based nursing evidence remains limited. This study evaluated the effect of home-administered celery juice on chronic pain and blood pressure among hypertensive older adults in the Gadingrejo Community Health Center, Pasuruan City, using the Gate Control Theory of pain as the theoretical framework. A quasi-experimental, non-equivalent two-group pretest–posttest design compared one adherent and one non-adherent patient over seven days. Both met identical inclusion criteria and received the same education and intervention offers. The intervention consisted of 200 mL of celery juice administered 1–2 times daily alongside standard nursing care. Pain was assessed using the Numeric Rating Scale (NRS), and blood pressure was measured with a calibrated sphygmomanometer before and after the intervention. Both patients had baseline pain scores of 6 and blood pressure of 160/100 mmHg. The adherent patient improved to a pain score of 3 with reduced blood pressure and better functional comfort, whereas the non-adherent patient improved only to a pain score of 5 with minimal blood pressure change. Regular celery juice consumption was associated with greater reductions in chronic pain and blood pressure, supporting its use as a safe, low-cost nursing adjunct when combined with sustained patient adherence.